Infrared Technology and Applications XLIV 2018
DOI: 10.1117/12.2304601
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of space radiation effects on HgCdTe avalanche photodiode arrays for Lidar applications

Abstract: We report the results from proton and gamma ray radiation testing of HgCdTe avalanche photodiode (APD) arrays developed by Leonardo DRS for space lidar detectors. We tested these devices with both ~60 MeV protons and gamma rays, with and without the read out integrated circuit (ROIC). We also measured the transient responses with the device fully powered and with the APD gain from unity to >1000. The detectors produced a large current impulse in response to each proton hit but the response completely recovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…From our model, we conservatively estimated an SNR of 250 for each lidar wavelength under sunlit conditions from a 50 km orbit with a 25‐cm diameter receiver telescope, 100 μJ output pulse energy per wavelength, and assuming a 1‐s integration time (Figure S11 in Supporting Information ). The laser and detector performance have been demonstrated for this wavelength regime using optical parametric oscillator‐based lasers (Cremons et al., 2020; S. X. Li et al., 2017), and a sensitive HgCdTe APD detector (Abshire et al., 2018; Hubbs et al., 2018; Sun et al., 2019). We do not intend to limit the lidar system or subsystem architecture here, but to ensure the simulations include reasonable measurement conditions for an orbital multispectral lidar.…”
Section: Methodsmentioning
confidence: 99%
“…From our model, we conservatively estimated an SNR of 250 for each lidar wavelength under sunlit conditions from a 50 km orbit with a 25‐cm diameter receiver telescope, 100 μJ output pulse energy per wavelength, and assuming a 1‐s integration time (Figure S11 in Supporting Information ). The laser and detector performance have been demonstrated for this wavelength regime using optical parametric oscillator‐based lasers (Cremons et al., 2020; S. X. Li et al., 2017), and a sensitive HgCdTe APD detector (Abshire et al., 2018; Hubbs et al., 2018; Sun et al., 2019). We do not intend to limit the lidar system or subsystem architecture here, but to ensure the simulations include reasonable measurement conditions for an orbital multispectral lidar.…”
Section: Methodsmentioning
confidence: 99%
“…The model uses the demonstrated laser pulse energy and width, optical receiver parameters, and the detector response and noise characteristics. The instrument parameters are listed in Table 1, and detector characteristics can be found in recent publications [59,65].…”
Section: Instrument Performance Modelmentioning
confidence: 99%
“…Radiation damage tests were also performed on the FPA's from the lot, which showed that these devices can be used in the space radiation environment of a typical Earth orbiting mission, provided that the FPAs can be annealed periodically by heating them to 85°C for a few hours. 9 The annealing can be achieved by including a small heater on the chip carrier inside the Dewar.…”
Section: Introductionmentioning
confidence: 99%